2019
DOI: 10.1155/2019/3246915
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics Model of an MR Damper including Magnetic Hysteresis

Abstract: Hysteresis is one of key factors influencing the output of magnetorheological (MR) actuators. The actuators reveal two primary sources of hysteresis. The hydro(mechanical) hysteresis can be related to flow dynamics mechanisms and is frequency- or rate-dependent. For comparison, the magnetic hysteresis is an inherent property of ferromagnetic materials forming the magnetic circuit of the actuators. The need for a good quality hysteresis model has been early recognized in studies on MR actuators; however, few st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Only control studies can thus be supported with it. That is in contrast with the multiphysics technique presented by Kubik and Gołdasz (2019) where the authors showed a hybrid finite-element/lumped parameter approach that can be employed at a design stage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Only control studies can thus be supported with it. That is in contrast with the multiphysics technique presented by Kubik and Gołdasz (2019) where the authors showed a hybrid finite-element/lumped parameter approach that can be employed at a design stage.…”
Section: Discussionmentioning
confidence: 94%
“…Second, it allows taking into account the effects already in the design process. For instance, Kubik and Gołdasz (2019), in the parametric study on the MR damper dynamic behavior with the so-called vector hysteresis approach, showed that the use of such models may yield improvements in understanding the MR damper physics and deliver a better product. Simply analyzing prior art, e.g., the study of hysteresis of an MR brake as in An and Kwon (2003) accomplished with the Hodgdon model highlights significant advantages in predicting the output of the brake on including the magnetic hysteretic operator.…”
Section: Introductionmentioning
confidence: 99%
“…Ansys for a magnetic model of the MR control valve. A more detailed description of this method is available in the document [1]. The presented transient magnetic model calculates the magnetic flux density response in the gap (air / MRF) on the current unit-step.…”
Section: Magnetic Modelmentioning
confidence: 99%
“…The magnetorheological (MR) damper utilizes magnetorheological (MR) fluid which, when subjected to magnetic stimuli, generates yield stress thus increasing its apparent viscosity [1]. MR fluid is a suspension of microsized ferromagnetic particles which are dispersed in the carrier fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The cohesion of chain formations causes an increase in the apparent viscosity of MR fluid [ 2 ]. This property is most often exploited by MR dampers [ 3 , 4 , 5 ], brakes/clutches [ 6 , 7 , 8 ], seals [ 9 , 10 ], or flexible structures [ 11 , 12 ]. The applicability of these MR devices in smart mechanical systems has several limitations.…”
Section: Introductionmentioning
confidence: 99%